Hypercholesterolaemia in children and young adults — current management - Frederick Raal (South African Family Practice)
Atherosclerosis begins in childhood. Not uncommonly, the first presentation of atherosclerosis is sudden cardiac death. It therefore makes sense that risk-factor modification to prevent the development or delay the onset of atherosclerosis needs to begin early in life. Dietary intervention is the key component for the primary prevention of hyperlipidaemia. However, if diet and lifestyle fail to correct hyperlipidaemia, drug therapy may have to be considered. All children and adolescents with high-risk lipid disorders such as familial hypercholesterolemia (FH), those with diabetes mellitus or other cardiovascular disease risk factors or with a family history of premature coronary artery disease should be considered for lipid-lowering therapy if diet and lifestyle intervention are ineffective. There are now numerous studies that have documented the safety and efficacy of statin therapy in both children and young adults. Based on these studies, it is now recommended that statin therapy be initiated in all male FH children from the age of ten years and at the onset of menses in females with FH. The initiation of statin therapy could be considered even earlier in FH children at high risk.